IKLAN PARTAI POLITIK DAN POLITIK MEDIA - Kheyene Molekandella Boer (Jurnal Visi Komunikasi, 2014)
Democratic National [NasDem] including a relatively new party stands now moreincentive to introduce her figure in the community by providing the intake-intake advertising invarious ways. At a time when society lost amid a crisis of confidence in the political world,NasDem born as an alternative option. The issue that was controversial was when RCTIprogram belongs under the auspices of HT is an event that crowned Miss Indonesia AstridEllena as Miss Indonesia 2011. Ellena also often pacing RCTI wearing NasDem parties belong,then Ellena also could say on behalf of the Lunar New Year pasrtai NasDem. Abuse is criticizedas less ethical manner, due to the utilization Ellena as Miss Indonesia should merelyambassadors of social, economic and cultural. Ellena must be free from pressure of any politicalparty, including NasDem although si-owner HT is one of the officials in the political parties.This paper describes the phenomenon of increasingly bablasnya ethics advertise due to thepressure of media ownership that ultimately melogiskan all the way to have the interests ofpolitical parties.Nasional Demokrat [NasDem] termasuk partai yang tergolong baru berdiri kini kiangencar memperkenalkan sosoknya pada masyarakat dengan cara memberikan asupan-asupaniklan dengan berbagai cara. Di saat masyarakat tengah kehilangan krisis kepercayaan dalamdunia politik, NasDem lahir sebagai alternative pilihan. Paper ini menjelaskan fenomena kianbablasnya etika beriklan akibat tekanan kepemilikan media yang akhirnya melogiskan semuacara demi mendapatkan kepentingan untuk partai politik.